2021
DOI: 10.1038/s41598-021-03566-4
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis for resistance to Striga hermonthica in diverse tropical maize inbred lines

Abstract: Striga hermonthica is a widespread, destructive parasitic plant that causes substantial yield loss to maize productivity in sub-Saharan Africa. Under severe Striga infestation, yield losses can range from 60 to 100% resulting in abandonment of farmers’ lands. Diverse methods have been proposed for Striga management; however, host plant resistance is considered the most effective and affordable to small-scale famers. Thus, conducting a genome-wide association study to identify quantitative trait nucleotides con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Some of the QTLs identified in this study have been reported in previous studies. For example, QTLs qSD 2.3 and qSD 5 detected for Striga damage, qSC 2.1 and qSC 2.2 for Striga emergence counts in this study have been previously reported by Stanley et al (2021) . The authors identified significant SNP markers S5_70442824 and S2_188120710 to be associated with Striga damage ratings as well as S2_135038935 and S2_208978140 associated with number of emerged Striga plants in a genome-wide association study to detect SNP markers linked with Striga resistance traits in late maturing maize germplasm.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Some of the QTLs identified in this study have been reported in previous studies. For example, QTLs qSD 2.3 and qSD 5 detected for Striga damage, qSC 2.1 and qSC 2.2 for Striga emergence counts in this study have been previously reported by Stanley et al (2021) . The authors identified significant SNP markers S5_70442824 and S2_188120710 to be associated with Striga damage ratings as well as S2_135038935 and S2_208978140 associated with number of emerged Striga plants in a genome-wide association study to detect SNP markers linked with Striga resistance traits in late maturing maize germplasm.…”
Section: Discussionsupporting
confidence: 81%
“…Several well-studied plant transcription factor families, including ethylene response factor (ERF), basic-domain leucine-zipper protein (bZIP), MYB, WRKY, NAC, and members of the basic helix-loop-helix (bHLH) transcription factors associated with defense responses in plants were identified in our study to be associated with Striga resistance adaptive traits. Stanley et al (2021) identified the bHLH transcription factors, putative leucine-rich repeat protein and bZIP transcription factors in a GWAS to identify Striga resistance linked markers using the IITA intermediate and late maturing maize inbred lines under artificial Striga infestation. Similarly; Gowda et al (2021) found the bHLH transcription factors to be associated with Striga resistance traits in maize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in maize and sorghum, most association mapping studies were based on population sizes not very far from our population size, e.g. n=132 ( Adewale et al., 2020 ), n=150 ( Stanley et al., 2021 ), n=169 ( Okunola et al., 2022 ), or n=173 (Kavuloko et al., 2021), in most cases using a single Striga population. Other studies used larger population sizes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A highly pleiotropic locus in GAP mass features included empty pericarp2 (Zm00001d005675), which is involved in embryo morphogenesis, shoot development, and the negative regulation of the heat shock response [49][50][51]. GAP expression data showed ZIMtranscription factor 8 (zim8, Zm00001d004277), a candidate gene for Striga damage [52], and kernel composition and popping expansion [53].…”
Section: Discussionmentioning
confidence: 99%